Hegemonia e mediação : um estudo sobre o trabalho cultural a partir do programa de TV Esquenta - Martins, Bruna Távora de Sousa (2015)
This paper presents, taking the example of the TV show Esquenta! , the mechanisms by hegemonic cultural organization that enable the television industry to be constituted as a space of mediation and hegemony. For this, we present the hegemony processes that has been carried out in Brazil since the imposition of Brazilian modernity and explains the work processes that allow the appropriation of cultural knowledge worker in this context, still pointing the systemic functions that the Industry cultural does in Brazilian capitalism. Thw work presents it by doing an analysis of the cultural labour and, its fundamental importance in the mediation process to promote a supportive cultural organization to implement an expansion of the economical system, and also the double appropriation operated on him. One, characterized by the generalization cultural relations of production and the submission of the mediation of this labour to the capitalist sector, which implies reflect on the hegemonic processes resulting from intellectual nature of this labor, and another defined by the internalization of a learning technique, which implies reflect on the appropriation of their knowledge in the consolidation of hegemonic models of cultural production.